Inherited and de novo SHANK2 variants associated with autism spectrum disorder impair neuronal morphogenesis and physiology - Berkel, Simone; Gass, Peter; Schratt, Gerhard; Rappold, Gudrun (Human molecular genetics, 2012)
Mutations in the postsynaptic scaffolding gene SHANK2 have recently been identified in individuals with autism spectrum disorder (ASD) and intellectual disability. However, the cellular and physiological consequences of these mutations in neurons remain unknown. We have analyzed the functional impact caused by two inherited and one de novo SHANK2 mutations from ASD individuals (L1008_P1009dup, T1127M, R462X). Although all three variants affect spine volume and have smaller SHANK2 cluster sizes, T1127M additionally fails to rescue spine volume in Shank2 knock-down neurons. R462X is not able to rescue spine volume and dendritic branching and lacks postsynaptic clustering, indicating the most severe dysfunction. To demonstrate that R462X when expressed in mouse can be linked to physiological effects, we analyzed synaptic transmission and behavior. Principal neurons of mice expressing rAAV-transduced SHANK2-R462X present a specific, long-lasting reduction in miniature postsynaptic AMPA receptor currents. This dominant negative effect translates into dose-dependent altered cognitive behavior of SHANK2-R462X-expressing mice, with an impact on the penetrance of ASD.
Gesehen am 04.04.2018